The Role of Perceived Relevance and Attention in Teachers’ Attitude and Intention to Use Educational Video Games - Sánchez-Mena, Antonio; Martí-Parreño, José; Aldás-Manzano, Joaquín (International Journal of Emerging Technologies in Learning (iJET), 2017)
Educational video games (EVGs) are becoming a trending topic in education as a new teaching methodology which can help teachers to increase students’ attention and engagement during the learning process. Nevertheless, despite an increasing academic interest in EVGs little research has been devoted to delve into teacher’s beliefs affecting their attitude towards EVGs and how these beliefs also affect their intention to use EVGs in their courses. Using Keller’s ARCS model as a theoretical framework, the role of perceived relevance and attention in teachers’ attitude and intention to use EVGs is analyzed. To do so a research model is tested using a sample of 312 Higher Education teachers via structural equation modeling to predict teachers’ attitude and behavioral intention to use EVGs in their courses. Results suggest that perceived attention drawn by EVGs is a factor affecting teachers’ intentions to use EVGs in their courses. Perceived relevance was not found to affect directly neither attitude nor intention to use while teachers’ perceived attention was found to affect teachers’ perceived relevance of EVGs. Limitations of the study, implications for managers, and future research lines are addressed at the end of the paper.